Bridging the Clinician/Researcher Gap with Systemic Research: The Case for Process Research, Dyadic, and Sequential Analysis. (13th October 2012) - Oka, Megan; Whiting, Jason
<x xml:space="preserve">Abstract</x> In Marriage and Family Therapy (MFT), as in many clinical disciplines, concern surfaces about the clinician/researcher gap. This gap includes a lack of accessible, practical research for clinicians. MFT clinical research often borrows from the medical tradition of randomized control trials, which typically use linear methods, or follow procedures distanced from "real‐world" therapy. We review traditional research methods and their use in MFT and propose increased use of methods that are more systemic in nature and more applicable to MFTs: process research, dyadic data analysis, and sequential analysis. We will review current research employing these methods, as well as suggestions and directions for further research.